(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Malaria in pregnancy is a major contributor to adverse maternal and perinatal outcome. In hyper-endemic areas like Nigeria, it is a common cause of anaemia in pregnancy in both immune and non-immune individuals and it has been aggravated by poor socioeconomic circumstances. This study determined the prevalence of malaria infection in relation to age group, gravidity and trimesters among pregnant women attending antenatal clinic in Primary Health Care Centers within Gombe metropolis, Gombe State. Four hundred (400) pregnant women, aged between 15-45 years voluntarily participated during study which was conducted in the rainy season from the months of June- September, 2015, when malaria infection is usually high. Blood samples were collected and then thin film was made and stained with Giemsa using parasitological standard procedure. Demographic data was collected using Chi-square to determine association between variables. The results showed very high prevalence of 91% for malaria among the study subjects. The finding showed that the difference was statistically significant (p<0.05) between malaria, gravidity and trimesters. But in the other hand, the difference was not statistically significant (p>0.05) between malaria and age group. It suggested routine mobilization and intensified antenatal care among pregnant women in order to avert complications associated with malaria parasites during pregnancy along with the distribution of Insecticide Treated Nets.